(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Among the legumes grown in Ukraine, chickpeas are a promising and competitive crop. This crop not only has high nutritional value but also plays a significant role in improving the agroecological condition of soils. Thanks to its ability to undergo symbiotic nitrogen fixation with nodule-forming bacteria, chickpeas facilitate the accumulation of biological nitrogen, which helps reduce the need for mineral nitrogen fertilizers. This, in turn, allows for lower production costs and minimizes the negative impact on the environment. Chickpeas are capable of producing high, consistent yields of adequate quality under extremely high air temperatures and prolonged moisture deficits during the growing season. In addition, including chickpeas in crop rotation helps improve the soil’s agrophysical and agrochemical properties, increase its fertility, stimulate microbiological processes, and create favorable conditions for growing subsequent crops. In this regard, chickpeas are considered not only a valuable food crop but also an effective biological factor in restoring soil fertility. Therefore, the issue of expanding chickpea acreage and improving cultivation techniques has become a pressing concern. The aim of the research was to determine the comprehensive effect of seed rates and sowing methods on the formation of the symbiotic system of chickpea plants of the Budzhak and Odysseus varieties during the growing season. Research Methods. The experimental studies were conducted at the «Experimental Field» Research and Training Center of the State University of Biotechnology in 2024–2025. The field trial was set up in accordance with standard procedures using two chickpea varieties, Budzhak and Odysseus. Five seed rates were studied – 500, 600, 700, 800, and 900 thousand seeds per hectare with three row spacing options: 15, 30, and 45 cm. Results. The studies established that the number and weight of nodules on plants of the studied chickpea varieties were significantly influenced by the tested seed rates and sowing methods. It was found that the maximum values of the studied indicators were reached during the flowering phase. Thus, in the Budzhak variety under the best treatment in the experiment, the number and weight of nodules were 20,2 and 0,95 g, respectively, and in the Odysseus variety, 21,1 and 1,03 g, respectively. During the branching, flowering, and ripening phases, the highest values for the number and weight of tubers were observed in the row-sowing variants with a row spacing of 15 cm and the minimum seed rate in the experiment—500,000 seeds per hectare. Thus, for the Budzhak variety, the number of tubers was 13,3, 20,2, and 10,9, and for the Odisey variety, 13,6, 21,1, and 11,1. Accordingly, the weight of tubers in the Budzhak and Odysseus varieties during the specified phases was 0,56; 0,95; and 0,48 g, and 0,59; 1,03; and 0,59 g, respectively. In both studied varieties, a tendency toward a decrease in the studied indicators was observed with an increase in the seed rate. Sowing methods also influenced the variability in the number and weight of formed tubers, but their effect was significantly smaller than that of seeding rates. It is worth noting that with the widening of row spacing from 15 to 45 cm, the maximum decrease in the number and weight of tubers was observed in all phases of measurement. Conclusions. It was found that the number of nodule-forming bacteria and their biomass per chickpea plant in both varieties under study decreased systematically with an increase in the seeding rate and row spacing. The maximum values of the studied indicators were observed during the flowering phase in the treatments with the minimum seeding rate of 500 seeds/ha. Thus, in the Budzhak variety, the number and weight of nodules were 20,2 and 0,95 g, respectively, and in the Odysseus variety, 21,1 and 1,03 g, respectively. Among the sowing methods studied, the row sowing method with a row spacing of 15 cm clearly demonstrated an advantage. Widening the row spacing from 15 cm to 45 cm resulted in a decrease in the number and weight of tubers by 1,9 pieces and 0,14 g in the Budzhak variety and by 2,2 pieces and 0,12 g in the Odisey variety.